A digital health intervention for young refugees: intervention development and initial dropout rates. (20th October 2021) - Fischer, L; Kölligan, V; Klein, M
Abstract: Background: Digital health interventions (DHI) have the potential to increase access to health care for vulnerable and hard-to-reach populations. As such, many refugees are at high-risk for mental health issues as well as underserved by health care systems of receiving countries, such as Germany. Interventions, digital or not, have shown to be more feasible and accepted if adapted to the specific needs of the targeted group. While evidence for the feasibility of DHIs among refugees is spare, studies show high dropout rates in DHIs in the general population. Methods: In a participatory and interdisciplinary approach, we developed a DHI for indicated addiction prevention, targeting young refugees from Syria, Iraq, Iran, and Afghanistan currently residing in Germany and with problematic use of alcohol and/or cannabis. This process consisted of a literature review, formative research, cultural adaptations of intervention elements, and ultimately the intervention's technical implementation following an iterative approach. The preliminary dropout rates immediately after download and during the baseline assessment were analysed using descriptive statistics. Results: The DHI, in form of the BePrepared App, was successfully developed and launched in January 2021 for entering a single-armed feasibility study. Preliminary results show a dropout rate of 46, 5% (n = 40) after download of the app and before entering the baseline assessment t0. Among the refugees reached and identified as such using the third item of t0, 73, 3% (n = 11) completed t0 and started the intervention (compared to 83.3% (n = 25) of the users without a self-declared refugee status). The further intervention dropout is to be determined. Conclusions: Adapting a DHI according to young refugees needs is to some extent possible. However, in accord with other DHI and regardless of the intervention content, dropout immediately after downloading the app (46.5%) and during the baseline assessment (58.1%) is high. Key messages: Within a set of further urgently needed interventions, DHIs are a low-threshold service that can increase access for refugees to mental health and substance use services. Considering high and early dropout, further research on reducing dropout from app-based DHI for refugees and other specific target group is needed to increase the feasibility of digital interventions.